Pressure drop across vortex diodes: experiments and design guidelines - Kulkarni, Amol A.; Ranade, Vivek V.; Rajeev, R.; Koganti, S. B. (Chemical Engineering Science, 2009)
Vortex diodes are used as leaky non-return valves in applications where it is desirable to avoid valves with moving parts. Despite their use in practice for several decades, no clear guidelines for design and optimization of vortex diodes are available. Detailed experimental study on flow and pressure drop characteristics of vortex diodes was therefore carried out to evolve such guidelines. The study covered a wide range of vortex diodes. The variation of diodicity (ratio of pressure drop for reverse and forward flow for the same flow rate) with respect to diode geometry, diode size (d(c)), aspect ratio (d(c)/h), nozzle configuration and Reynolds number (Re) was studied. The experimental results were critically analyzed to develop a design methodology. The methodology is shown to be useful for obtaining the diode dimensions that would yield the desired diodicity for the required operating flow rate. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Aspect ratio; Diodicity; Nozzles; pressure drop; Vortex diode

pH-Dependent single-step rapid synthesis of cuo and cu2o nanoparticles from the same precursor - Nikam, Arun V.; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam; Kulkarni, Amol A.; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2014)
A single-step protocol to prepare Cu2O and CuO nanocrystalline particles from the same precursor by microwave irradiation has been developed using the pH of the solution as the only variable parameter. The utility of different bivalent Cu-precursors for synthesis of CuO and Cu2O nanoparticles was also investigated. The morphology, phase purity, and optical properties of these nanoparticles were analyzed using TEM, SEM, XRD, and optical spectroscopy. The band edges were determined using cyclic voltammetry. Field effect transistors based on CuO nanoparticles showed a hole mobility of 3.5 x 10(-2) cm(2) V-1 s(-1), making them a suitable candidate for energy-related applications. The effect of hydrazine vapor exposure on the IV-characteristics of CuO nanoparticles was also investigated. This revealed a decrease in source current with respect to time.

Perspective article: flow synthesis of functional materials - Sebastian, Victor; Khan, Saif A.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2017)
Continuous-flow synthesis of specific functional materials is now seen as a reliable synthesis approach that gives consistent product properties. This perspective article aims to survey recent work in some of the relevant areas and to identify new domains where flow synthesis of functional materials can be better than the conventional synthesis methods. It also emphasizes the need for developing high-throughput integrated synthesis and screening systems for almost all functional materials so that laboratory-scale recipes can be transformed into reliable manufacturing processes. New areas relevant to functional materials which have remained unexplored in flow synthesis are also highlighted.

Pinched tube flow reactor: hydrodynamics and suitability for exothermic multiphase reactions - Sharma, Mrityunjay K.; Potdar, Shital B.; Kulkarni, Amol A. (AIChE Journal, 2017)
A novel tubular flow reactor where a straight tube is modified by pinching it periodically at a fixed pitch and at different angles is presented. Pinched tubes (straight tube as well as helical coils) with different pitch and angles between successive pinching are studied. This work reports a detailed hydrodynamic study involving single and two-phase flow. Mixing experiments showed that having an angle of 90° between successive pinchs achieves the shortest mixing length when compared to lower angles. Pressure recovery along with sequence of high and low shear zones and change of flow direction imposed better mixing. Residence time distribution studies showed that higher number of pinch sections decreases the extent of dispersion, yet it deviates from plug flow. The performance is evaluated by carrying a homogeneous and two-phase aromatic nitration and also liquid-liquid extraction. Pinched tube presents an economical option as a flow reactor for conducting exothermic reactions. © 2016 American Institute of Chemical Engineers AIChE J, 2016
Keywords: pinched tube flow reactor; pressure drop; residence time distribution; mass transfer; reactions

Pressure equalization approach for flow uniformity in microreactor with parallel channels - Madane, Ketan; Kulkarni, Amol A. (Chemical Engineering Science, 2018)
Numbering-up using parallel channels helps to achieve higher processing capacity while retaining the advantages of microreactors. However it may also lead to non-uniformity in flow across all the channels. Here we report the CFD simulations and experimental observations on the extent of uniformity in the flow from an assembly of several parallel channels. In the conventional parallel channel geometry, smaller channel size (<300 m) as well as higher fluid viscosity is seen to give better flow uniformity. Inequality in pressure distribution at the inlet of a large number of parallel channels is overcome by having two `pressure equalization slots' at an equal distance from inlet and outlets that open in the respective manifolds. Having such an arrangement helped to reduce the standard deviation in the flow by almost 90% when compared to the conventional geometry. However the modification was seen to increase the extent of back mixing to some extent. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: CFD; Experiments; Flow distribution; microreactor; Numbering-up; Parallel channels